Пам’ятки осілості скіфського часу на острові Хортиця - Остапенко, М.А. (Археологія, 2001)
У статті розглядаються основні напрями розвитку господарства скіфського населення, яке мешкало в VI-III ст. до н. е. на найбільшому дніпровському острові — Хортиці. В статье вводятся в оборот материалы скифской эпохи, выявленные в последние годы на о-ве Хортица (южная часть Днепровских порогов). Используя материалы городища, поселений, грунтовых могильников и переправ, автор выделяет основные направления хозяйства хортицких скифов. Анализ предметов материальной культуры позволяет сделать вывод о значительном сходстве рассмотренных памятников с конгломератом поселений оседлых (или полуоседлых) скифов Степного Поднепровья. Сконцентрированность скифских объектов на острове и определенная оторванность от основного массива памятников Каменско-Никопольского района позволяет выделить Хортицкий эколого-экономический район скифской оседлости. The paper sums up the materials of the Scythian period found during the last years on the Khortytsia island (the south region of the Dnieper rapids). By using the materials from the fortress, sites, ground burials, and crossings, the author indicates the main directions of development of Khortytsya’s Scythian economy. The analysis of things of the material culture allows one to conclude about a considerable similarity between Khortytsya’s sites and the conglomeration of settlements of the settled (semi-settled) Scythians in the Mid Dnieper region. The concentration of Scythian objects on the island and their certain isolation from the basic massif of monuments of the Kamenka-Nikopol district allow us to distinguish the Khortytsya ecological and economic settled-life area of the Scythians.